The Hansen’s disease and its diagnostic process - Santos, Danielle Christine Moura dos (2007)
The early diagnosis of Hansen’s disease is one the essential conditions for the disease control. This study has as an objective to identify on the report of the Hansen’s disease carriers the main problems faced to the early diagnosis of the disease. Qualitative methodology was employed with analysis of semi-structured interviews made with carriers in the Sanitary  dermatology ambulatory – CISAM, Recife – PE. 21 patients were interviewed aged within 9 and 73 years old. Most of them presented late diagnosis of the disease. The situations that delivered to this were grouped in 4 categories for analysis: Hansen’s disease stigma, being-ill perception, knowledge about the disease, the health assistance search. The last category was the most occurred, where patients took until 3 years from the first health service search to the diagnosis. Four patients had only noticed traces of the disease when it was already transmissible, others had no or precarious knowledge about the Hansen’s disease and delayed the health service search. Hansen’s disease must be diagnosed in its undetermined initial  phase due to interrupt the “transmission chain” and avoid the evolution to more critical cases. So, the population must know the traces and symptoms of the disease and be motivated to look for the health service, which must be prepared with qualified professionals.